Ex Post Bargaining, Corporate Cash Holdings, and Executive Compensation. (21st May 2022) - Cheng, Yingmei; Harford, Jarrad; Hutton, Irena; Shipe, Stephan
Abstract: We show that high cash holdings can be used by executives in the ex post bargaining over their compensation. Cash holdings are positively associated with CEO compensation and is driven by non-salary components. In companies with weaker governance, this relation is more pronounced. Using exogenous shocks to the firm's cash, we show that CEO compensation readily responds to increases in cash holdings, confirming that managers are able to derive personal benefits from excess cash holdings.